Cerebral blood flow assessment of preterm infants during respiratory therapy with the expiratory flow increase technique - Mariana Almada Bassani; Jamil Pedro Siqueira Caldas; Abimael Aranha Netto; Sérgio Tadeu Martins Marba (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To assess the impact of respiratory therapy with the expiratory flow increase technique on cerebral hemodynamics of premature newborns. Methods: This is an intervention study, which included 40 preterm infants (≤34 weeks) aged 8-15 days of life, clinically stable in ambient air or oxygen catheter use. Children with heart defects, diagnosis of brain lesion and/or those using vasoactive drugs were excluded. Ultrasonographic assessments with transcranial Doppler flowmetry were performed before, during and after the increase in expiratory flow session, which lasted 5min. Cerebral blood flow velocity and resistance and pulsatility indices in the pericallosal artery were assessed. Results: Respiratory physical therapy did not significantly alter flow velocity at the systolic peak (p=0.50), the end diastolic flow velocity (p=0.17), the mean flow velocity (p=0.07), the resistance index (p=0.41) and the pulsatility index (p=0.67) over time. Conclusions: The expiratory flow increase technique did not affect cerebral blood flow in clinically-stable preterm infants.